Elastic LIDAR Monitoring of the Night-sky Brightness over Roque de los Muchachos Observatory. Issue 1 (1st December 2022) - Pavletić, Lovro; Gaug, Markus; Fruck, Christian; Hahn, Alexander; Acciari, Victor; Besenrieder, Jürgen; Prester, Dijana Dominis; Dorner, Daniela; Fink, David; Font, Lluís; Mićanović, Saša; Mirzoyan, Razmik; et al.
Abstract: Every large world-class observatory must operate in a very dark environment that is as free as possible of anthropogenic sources of light pollution, which can degrade the quality of ground-based astronomical observations. A LIDAR is able to measure, and subtract from its laser return signals, a corresponding contribution from the night-sky brightness. Our elastic LIDAR system is operated in semi-continuous mode at night, very closely following the observation schedule of the MAGIC Telescopes on Canary island La Palma, Spain. For the monitoring of the night-sky brightness, median LIDAR background rates at different atmospheric conditions and sky illuminations have been used. In this talk, results from data taken with the MAGIC LIDAR over seven years, from March 2013 until March 2020, will be presented and discussed.